Dexter. / The final season [videorecording (DVD)]. - Lindsay, Jeffry P.
Season eight begins six months after LaGuerta's murder, and Dexter is still managing life as a dad, brother, and serial killer. As Deb struggles to deal with the consequences of her actions, a mysterious woman comes to work with Miami Metro, offering firsthand information on Dexter's past.